Advanced Revit architecture 2015 training - Myers, Brian; Safari eBooks ([S.l.] : InfiniteSkills, 2014)
"In this advanced Revit Architecture 2015 training course, expert author Brian Myers takes you beyond the basics of Revit Architecture and shows you how to leverage the features in this powerful software from Autodesk. This course is designed for users that already have a working knowledge of Revit. You will start by learning how to properly define families and parameters, set up annotation standards, and link Revit files. Brian will teach you how to create phases, view templates and filters, and work with the site tools. You will learn how to perform mass studies, apply advanced wall techniques, work with floors, stairs, and ramps, make and edit railings and roofs, and add ceilings. This video tutorial will teach you how to group components, create and modify parts and assemblies, and plan the area and volume of a room. Finally, you will learn how to add detail components to your projects, prepare them for presentations, and share your work using Worksharing. Once you have completed this computer based training course, you will have a strong, fundamental understanding of the tools and techniques available to you in Revit Architecture. Working files are included, allowing you to follow along with the author throughout the lessons. "--Resource description page.
Title from resource description page (viewed July 16, 2014).
Presenter, Brian Myers.
Keywords: Autodesk Revit; Computer-aided design; Architectural drawing; Electronic books